2019
DOI: 10.1017/jfm.2019.664
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamically consistent modelling of two-phase flows with moving contact line and soluble surfactants

Abstract: Droplet dynamics on a solid substrate is significantly influenced by surfactants. It remains a challenging task to model and simulate the moving contact line dynamics with soluble surfactants. In this work, we present a derivation of the phase-field moving contact line model with soluble surfactants through the first law of thermodynamics, associated thermodynamic relations and the Onsager variational principle. The derived thermodynamically consistent model consists of two Cahn–Hilliard type of equations gove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 121 publications
(50 citation statements)
references
References 74 publications
0
50
0
Order By: Relevance
“…It has been applied to solidification dynamics, viscous fingering, fracture dynamics, vesicle dynamics, etc. The method substitutes boundary conditions (matching conditions) at the interface by a partial differential equation for the evolution of an auxiliary field (the phase field) that acts as an order parameter [100][101][102]. A phase-field model is usually constructed in such a way that in the limit of an infinitesimal interface width (the so-called sharp interface limit), the correct interfacial dynamics are recovered.…”
Section: Numerical Simulation On Pipeline Scaling With Different Injementioning
confidence: 99%
“…It has been applied to solidification dynamics, viscous fingering, fracture dynamics, vesicle dynamics, etc. The method substitutes boundary conditions (matching conditions) at the interface by a partial differential equation for the evolution of an auxiliary field (the phase field) that acts as an order parameter [100][101][102]. A phase-field model is usually constructed in such a way that in the limit of an infinitesimal interface width (the so-called sharp interface limit), the correct interfacial dynamics are recovered.…”
Section: Numerical Simulation On Pipeline Scaling With Different Injementioning
confidence: 99%
“…SEM images from Eagle Ford shale samples showed that pores are mainly round, angular, and slitshaped pores (Afsharpoor and Javadpour, 2016;Song et al, 2019). In conventional oil and gas reservoirs, using circular pores approximation to represent actual pore type is reasonable because the pore surface-to-volume ratio in conventional reservoirs is small (Zhu et al, 2019). In shale reservoirs, pores have a large surface-to-volume ratio.…”
Section: Introductionmentioning
confidence: 99%
“…We can directly obtain chemical potentials through variational derivatives of the free energy functional with respect to two phase-field variables. Two Cahn-Hilliard-type equations can be adopted to describe the evolutions of two phase-field variables (Liu et al, 2018;Zhu et al, 2019c). The hydrodynamics coupled phase-field surfactant model can be obtained if two Cahn-Hilliard-type equations are further coupled to the Navier-Stokes equation.…”
Section: Introductionmentioning
confidence: 99%